Impacto do acompanhamento farmacoterapêutico na adesão ao tratamento e no controle metabólico e inflamatório de pacientes com Diabetes Mellitus tipo II - Santos, Mayara Paes (2018)
The aim of this study was to evaluate the impact of pharmacotherapeutic follow-up on adherence to treatment and on metabolic and inflammatory parameters in patients with T2DM. This was a prospective interventional study, in which 60 patients diagnosed with T2DM were selected from Family Health Units in the Maruípe territory of the city Vitória-ES. Patients received pharmacotherapeutic follow-up with individual guidelines every 2 months for a period of 6 months. For the pharmacotherapeutic follow-up, an adaptation of the SOAP methodology (Subjective, Objective, Evaluation and Plan) was used, and the Morisky-Green (TMG) and MedTake (MTT) tests were used to evaluate adherence and knowledge of the treatment. Clinical and anthropometric parameters were measured during pharmacotherapeutic follow-up. Biochemical parameters were investigated through tests of fasting glycemia, glycated hemoglobin, lipid profile, creatinine, gamma-GT, urea and uric acid. The inflammation evaluation was performed through the inflammatory markers: fibrinogen, C-reactive protein (CRP), interleukin-6 (IL-6), and tumor necrosis factor alpha (TNF-α). In addition, polymorphisms were investigated in the promoter regions of the fibrinogen (-148 C/T), IL-6 (-174 G / C) and TNF-α (-308 G/A and -238 G/A) genes. In this study, a significant increase (p <0.0001) in adherence and knowledge to the treatment after pharmacotherapeutic follow-up was found. Regarding the pharmacological treatment, patients improved (p <0.05) MTT for metformin, insulin and gliclazide, in TMG questions and in adherence to the types of treatments for T2DM, evidencing an improvement in adherence and knowlegde to the treatment. In addition, no significant changes in metabolic control, systolic and diastolic blood pressure, body mass index, weight, waist circumference, and capillary glycemia were observed. However, there was a significant increase for HDL-c levels and waistto-hip ratio (WHR). Regarding inflammatory markers, only fibrinogen significantly reduced (p = 0.0224). CRP, IL-6 and TNF-α did not suffer significant changes (p> 0.05). Polymorphism genes (SNPs) were not shown to be influential in plasma levels of fibrinogen, IL-6 and TNF-α (p> 0.05). Therefore, pharmacotherapeutic follow-up was relevant because it contributed to the improvement of adherence to treatment, knowledge about medications and levels of HDL-c and fibrinogen in patients with T2DM.